Strategic Devises to Enhance Accounting Cash Journals Content Knowledge of Economic and Management Sciences Teachers - Mojakgomo David Moloi; Malose Kola; Habasisa Vincent Molise (Research in Social Sciences and Technology- OpenED Network, 2023)
This paper investigated the strategic devices that can be used to enhance the accounting cash journals content knowledge (ACJCK) of Grade 9 economic and management sciences (EMS) teachers. The study was qualitative, with three participants selected from one rural school in the Thabo-Mofutsanyane education district. The interviews were used to gather information regarding the strategic devices that can be used to enhance the ACJCK of EMS teachers. The data were then analysed using thematic analysis. Finally, the study revealed the following findings: create professional learning communities to enhance cash journals content knowledge and ensuring collaborative lesson planning and preparation of cash journals. The findings suggest that collaborative team teaching must be used to accommodate novice teachers, and continuous training workshops and cluster workshops should also be used to increase teachers’ level of understanding to address the inherent cash journal content knowledge misconceptions.